Changing Pattern of Forests in Haryana: Assessing the Rapid Deforestation and Changes in Forest Area in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Forest resource conservation has been widely accepted as a key to sustain the local and regional economic development. The forest edges are affected by anthropogenic activities including deforestation, forest fragmentation, selective logging, extraction of non-timber forest products, collection of medicinal plants, recreations, hydroelectric projects and its associated developmental activities, which alter the biodiversity. The present study reveals that actual situation of forests and comparison between different districts regarding area under forests in the state of Haryana. The result of study says forests are in the critical situation in the state of Haryana and deforested very rapidly. Present study is very useful for making environment policies for the state based on district wise changes of forests area.